Folate and Vitamin B12 Levels in Thai Patients with Oral Lichenoid Related Drug - Kobkan Thongprasom; Tin Panyawaraphon; Thanapat Pathomkulmai; Sahaphon Hungsaprug (Acta Stomatologica Croatica, 2015)
Medications have been increasingly used by patients for the treatment of their systemic diseases. However, many drugs are reported to induce oral lichenoid lesions (OLL). Aim: The aim of our study was to investigate the relationship between OLL, medications, and folate and vitamin B12 levels. Material and Methods: Twenty Thai patients who were diagnosed with OLL by clinical and histopathological examination were included in this study. These subjects were compared with 24 healthy control subjects. Complete blood counts, hemoglobin typing, serum and red cell folate, and serum vitamin B12 levels were investigated. The medications taken and the systemic diseases of the Thai patients with OLL were recorded and analyzed. Results: Our results showed that only 1/20 patients with OLL (5%) had low red cell folate and only 1 case showed a low level of serum folate. Vitamin B12 levels were within normal range in both groups. There were no significant differences in red cell folate, serum folate, or vitamin B12 levels between the patients with OLL and the control group (p>0.05). Four cases in OLL and 3 cases in the control group had low hematocrit less than 36% and they were defined as anemic. Conclusion: Antihypertensives and hypolipidemics were the most common medications taken by patients with OLL; however, these drugs had no effect on red cell folate, serum folate, or vitamin B12 levels. Since the patients were taking multiple drugs and we could not confirm the diagnosis of OLDR by withdrawal of the drugs, we used the term OLL related drug instead.